2019
DOI: 10.1177/0194599819892015
|View full text |Cite
|
Sign up to set email alerts
|

Distance Traveled to Head and Neck Cancer Provider: A Measure of Socioeconomic Status and Access

Abstract: Objective Improved head and neck cancer survival has been associated with traveling farther distances for treatment, potentially due to patients seeking higher-quality facilities. This study investigates the role of both facility and confounding patient factors on this relationship. Study Design Review of national registry data. Setting National Cancer Database. Subjects and Methods Adults with head and neck cancer diagnosed from 2004 to 2014 were identified. Overall survival was compared among distance-to-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 26 publications
4
43
2
Order By: Relevance
“…Consistent with our observations, previous studies have shown that reduced access to care, as measured by travel time to treating facility, is related to SES 49,50 . One study found that access to care, as measured by insurance status, was the most important factor associated with racial differences in HNSCC 5‐year survival 31 .…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our observations, previous studies have shown that reduced access to care, as measured by travel time to treating facility, is related to SES 49,50 . One study found that access to care, as measured by insurance status, was the most important factor associated with racial differences in HNSCC 5‐year survival 31 .…”
Section: Discussionsupporting
confidence: 90%
“…22 Other studies have not found an association between rural residence and cancer survival for ovarian 23 and head and neck cancer. 24 Survival results from NCDB studies for residential distance to the diagnosis reporting hospital are mostly in contrast to our results, with the exception of CNS tumors, with studies showing that longer distance is associated with improved survival outcomes for head and neck, 25,26 gastrointestinal, 27 rectal, 28 prostate, 29 and gallbladder, 30 but not ovarian 31 cancers. Superior survival for some cancers may possibly be explained by treatment at an academic medical center or a high-volume center.…”
Section: Cancer October 1 2021contrasting
confidence: 99%
“…It is also well established that health outcome disparities between patients of different races are largely related to a myriad of socioeconomic factors such as marital status, income, education level, insurance status, and distance to treatment facility. 6,[12][13][14][15][16][17][18] In a recent study by Shin et al that controlled for various factors, race was still found to independently predict overall mortality (OM) of laryngeal squamous cell carcinoma (LSCC) in the United States. 19 Historically, Black patients have had lower survival in the United Sates.…”
Section: Introductionmentioning
confidence: 99%